Functionalization of polyethyleneterephthalate fibers using galactoglucomannan from spruce wood. Issue 2 (January 2016) - Šauperl, Olivera; Doliška, Aleš; Hadela, Ajra; Strnad, Simona
Interest in researching biopolymers from renewable resources has risen over recent decades. Biopolymers that are byproducts within industrial production processes are of special importance, thus there is no need for additional fertile soil for their production. During the production of thermo-mechanical pulp within the paper industry, galactoglucomannans (GGMs) are dominant hemicelluloses and are released in large quantities in the processing of water as a byproduct. In this research a new possibility was investigated for the application of GGM from spruce wood. The influence of GGM adsorption from aqueous solutions onto polyethyleneterephthalate (PET) fibers on their surface properties and hydrophilic/hydrophobic character was thoroughly analyzed. The adsorption process was analyzed and optimized using quartz crystal microbalance with a dissipation unit. Total organic carbon determination was applied for evaluating the success of GGM adsorption onto PET fabric samples. The hydrophilic/hydrophobic character of treated fabrics was evaluated by moisture sorption determination as well as by water adsorption determination using tensiometry and water contact angles determination using goniometry. The results showed that even small amounts of adsorbed GGM significantly increased the hydrophilicity of PET fabric samples. Moisture content within standard atmosphere was increased by about 100%, water adsorption by about 250% and water contact angles were decreased from 125° to immediate spreading when comparing non-treated PET fabric with a GGM-treated one. The presented research proved the hypothesis that GGM from spruce wood is potentially highly applicable for functionalization of synthetic textile materials in order to significantly increase their surface hydrophilic characteristics.